Exploring the Role of Incidental and Integral Compassion and Anger in Health Communication about Pollution - Lu, Hang (Health communication, 2020)
Scholars have examined two types of emotions, namely, incidental and integral emotions, in health communication on the basis of the source of elicitation. Despite numerous studies on the independent effects of these two types of emotions, limited research exists on how emotions may interact to influence health communication outcomes, including support for health-improving policies. To augment current knowledge, this study conducted a 2 (incidental: compassion vs. anger) × 2 (integral: compassion vs. anger) between-subjects factorial experiment in the context of the human health effects of pollution. Results showed a main effect of the incidental compassion (vs. anger) condition on protective policy support, which was mediated by self-reported compassion. In addition, this main effect was moderated by political ideology such that it was found among moderates and conservatives, but not liberals. No interaction effects were observed. These findings contribute to the literature by exploring how incidental and integral emotions may or may not interact and by complementing existing research on the moderating effect of political ideology regarding environment-related messaging.